Data for DPhil Thesis: 'The Reactivity of Strained Carbocycles' by Alistair J Sterling - Sterling, A J (University of Oxford, 2021)
These data contain three directories, corresponding to Chapter 2–4 of the DPhil Thesis of Alistair J Sterling. Each directory contains Cartesian coordinates of all calculated stationary points as xyz files, as well as an Excel spreadsheet containing the energies of all calculated species. Additionally, /Chapter2/ contains a directory 'MOJ_plot' which contains a Python 3 script 'main.py' and csv file 'data.csv' to generate the More O'Ferrall Jencks plot, and /Chapter4/ contains a directory 'MLR_plots' with a Python 3 script 'main.py' and three csv files ('amide_data.csv'; 'Hoz_data.csv'; 'hydrocarbons_data.csv') to generate the (multiple) linear regression plots.